KEBANGKITAN POPULISME DI AMERIKA LATIN - , Imelda Masni Juniaty S ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines the phenomenon of the rise of populism in Latin America that occurred in the late 1990s until the 2000s. This phenomenon is interesting because the two previous decades the experts have claimed that populism in Latin America has "ended". By placing populism in political perspective, this study tried to find out the trigger of reemergence of populism in Latin America and found a pattern of populism that emerged in the late 1990s until the 2000s. This study found that there are two main things that trigger the reemergence of populism in Latin America. They are the practice of economic exclusion and political exclusion by the regime of neoliberalism towards the lower social classes, and also the weak of institutions (political parties and governments) in response to new problems. The practice of economic and political exclusion by the regime of neoliberalism provided an opportunity for the populist leaders to mobilize the lower social classes in order to oppose the ruler. The loss of the governmentâs capability to address the socioeconomic and political crisis gives a chance to the populist leaders to overthrow the regime of neoliberalism in order to achieve power. To achieve power, there are two paths that the populist leaders have. First, build alliances with the lower social classes that are not organized. This pattern is called the irrational populism. Second, build alliances with the lower social classes that are well organized that are called the rational populism. The first pattern is reflected in the case of Chavez's rise to power while the second pattern is reflected in the case of Lula, Kirchner and Morales.